Optimization of Remote Intake Pump Control System Using MQTT Protocol Based on PLCnext (Case Study : Pluit Reservoir) - Pranoto, Fransisxus Wisnu (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2026)
This research was motivated by operational inefficiencies in the intake pump control system at Pluit Reservoir, caused by the 1.4 km distance between the Water Treatment Plant (WTP) and the pump house, as well as the failure of a previous fiber optic-based control system and the performance limitations of an HTTP-based system. This study aims to optimize the remote control system by comparing the performance of the Message Queuing Telemetry Transport (MQTT) protocol with the Hypertext Transfer Protocol (HTTP) on the PLCnext AXC F 2152 platform. The research method used was experimental, involving the construction of a control system prototype that represents field conditions and conducting tests under unstable internet network scenarios. The Quality of Service (QoS) parameters measured included throughput, packet loss, delay, and jitter. The results show that the MQTT protocol is significantly superior in terms of reliability and responsiveness. Under unstable network conditions, MQTT was able to suppress packet loss to below 1%, whereas HTTP experienced packet loss of up to 40%. Furthermore, the delay on MQTT was recorded to be 2-3 times lower than HTTP, making it far more responsive for realtime control applications. Although HTTP's throughput is inherently higher, MQTT's superiority in minimizing packet loss and delay proves that it is a more optimal and reliable solution for critical infrastructure control systems in environments with limited connectivity.